If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -3 = 7b Reorder the terms: -3 + 4b = 7b Solving -3 + 4b = 7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-7b' to each side of the equation. -3 + 4b + -7b = 7b + -7b Combine like terms: 4b + -7b = -3b -3 + -3b = 7b + -7b Combine like terms: 7b + -7b = 0 -3 + -3b = 0 Add '3' to each side of the equation. -3 + 3 + -3b = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -3b = 0 + 3 -3b = 0 + 3 Combine like terms: 0 + 3 = 3 -3b = 3 Divide each side by '-3'. b = -1 Simplifying b = -1
| (2b+9)=3 | | x+5+3x-7=180 | | 2(x-3)=2x+15 | | -3=x/-3-2 | | 3x+2x^2+5x= | | -9+11p=19+13p | | 5/12x4 | | 7x^2-14x+10=3 | | 14/(2-x | | 13q-2=-19+14q | | 9n^2=5+4n | | 50=28.1+.15m | | 12z-10z-2=2 | | 5x+6x-2x=43+2 | | rv+3*1v-3=0 | | 7-2.5x=13 | | 1.09(1.23)(7-x)=9 | | (X-28)+(2x-79)+(.5x+14)=180 | | 4x^2-30x+44=0 | | 50=36.5+.1m | | 150=2x+5(-7x-3) | | 2(p+3)=14 | | -2x+8=-144 | | -14f=-13f-14 | | 19x+12=18x+3 | | 4j-9j+j-4j-5= | | 2/3x^2-7=46 | | 0.2(18)+0.05x=0.1(24+x) | | -15d-12=-14d | | 3f-2+f-6= | | -5x+18+3(x-1)=8x-(7x-9)-6x+6 | | -4v-9=-6-v |